Avaliação do potencial alelopático dos extratos foliares brutos do capim-annoni-2 (Eragrostis plana Nees) e estudo do óleo essencial - Dalbosco, Talita (2013)
The grass - 2 lovegrass , Eragrostis plana Nees , is an African plant species known for its invasive capacity and , therefore , classified as a weed , and is considered the most aggressive and more difficult to control in the southern fields . This species active mechanisms of inhibition of germination and growth of neighboring species in the phenomenon called allelopathy . The phytochemical study of E. plana Nees , is justified because it is a species with alleged allelopathic activity and, depending on its characteristics and the biological and economic impact caused by it . In order to identify and characterize bioactive molecules and evaluate their allelopathic effects , the experiments were performed . The leaves of E. plana Nees were collected in winter and summer , for phytochemical analysis , and obtain the essential oil sample was taken by hydrodistillation and subsequently filtered and chilled to the gas chromatographic analysis coupled with mass spectrometry . For non- volatile secondary metabolites , the plant material was subjected to exhaustive cold extraction with petroleum ether and ethyl acetate . The extracts were subjected to IR technique . In allelopathic identification seeds of Ipomoea grandifolia species commonly performed in two bioassays in allelopathic studies were used . The tests , germination and radicle and hypocotyl elongation were monitored daily for 7 days under controlled and conducted in chambers BOD ( Biochemical Oxygen Demand ) conditions . For both tests 5 doses with different concentrations of each extract volume of 5 mL in each Petri dish were used. The experimental design was completely randomized with 4 replications, with distilled water and Tween 80 + solvent extractors as witnesses . The data were submitted to variance homogeneity test, the Cochran C and analysis of normality by the Shapiro - Wilk test, with subsequent analysis of variance , ANOVA and Tukey test at 5 % significance level for the homogeneous variables. The allelopathic effect exhibited by the leaves of E. Nees plane can be related to the levels observed in the analysis of terpenes of essential oil , since they possess allelopathic effects , as reported in the literature. The extracts expressed the allelopathic potential of E. plana Nees , interfering with the development of the receiving species . The use of these extracts directly or as a source of chemical molecules , can collaborate in developing new bio - herbicides.